A coparative study of single phot . hjerapy plus white curtains and sigle phototherapy in term newborns with hyerrilirubinaemia - Djokomuljanto, Stanislaus (2008)
To determine whether the addition of low-cost reflecting curtain to a standard phototherapy unit could increase effectiveness of phototherapy for neonatal jaundice. Randomized controlled clinical trial. Level one nursery of the Hospital Universiti Sains Malaysia, Kelantan, Malaysia. Term newborns with uncomplicated neonatal jaundice presenting in the first week of life. Phototherapy with white curtains hanging from the sides of phototherapy unit (study group, n=50) was compared with single phototherapy without curtains (control group, n=47). The primary outcome was the mean difference in total serum bilirubin measured at baseline and after 4 hours of phototherapy. The secondary outcome was the duration of phototherapy. The mean (standard deviation) decrease in total serum bilirubin levels after 4 hours of phototherapy was significantly (p<0.001) higher in the study group [27.62 (25.24) J.tml/L] than in the control group [4.04 (24.27) J.tml/L]. Cox proportional hazard regression analysis indicated that the median duration of phototherapy was significantly shorter in the study group ( 12 hours) than in the control group (34 hours; i change 45.2; p<0.001; hazards ratio 0.20; 95% confidence interval 0.12 to 0.32). No difference in adverse events was noted in terms of hyperthermia or hypothermia, weight loss, rash, loose stools or feeding intolerance. Hanging white curtains around phototherapy units significantly increase the efficacy of phototherapy in the treatment of neonatal jaundice without evidence of increased adverse effects.